Artificial and natural weathering of ABS - Santos, R. M. (2010)
Acrylonitrile-butadiene-styrene (ABS) is a complex copolymer with exceptional importance in technological applications. However, ABS is known to present a high susceptibility to weathering when exposed to UV radiation in the presence of oxygen. In this work, photodegradation of ABS was studied under natural and accelerated conditions. Exposed samples were removed periodically and characterized by several analytical techniques. During both types of weathering chemical modifications occurs mainly at the surface, which affects considerable the optical, mechanical, and rheological properties. The results obtained evidence that during accelerated weathering the formation rate of photodegradation products is higher when compared to natural weathering results. However, chain scission occurs mainly along natural conditions.